GENERATION X's EFFECTIVE LEADERSHIP IN ADDRESSING XYZ'S CROSS-GENERATIONAL GAP IN CREATIVE INDUSTRY COMPANIES - Caroline Angela Randabunga; Rudi Sukandar (INFOKUM, 2022)
This study aims to examine effective leadership in revealing effective leadership styles in multi-generational corporate environments such as XYZ. This qualitative research was conducted through in-depth interviews of researchers on a creative industry company by interviewing 3 Managerial Teams who are in generation X at PT. X who has team work from each generation X, Y and Z personally. The instruments used in this qualitative research are centered on observation and face-to-face interviews. The researchers' hope that this research can expand generational education for leadership while maintaining a legacy of individuality in organizations can correct possible generational barriers.